Body Perception: Parents Poorly Perceive Children’s Fitness Characteristics - Elan Joshua Lieber (The Journal of Undergraduate Research, 2013)
At least 155 million school-age children worldwide are overweight or obese. Body Mass Index (BMI) as a measurement of parental recognition of child’s overweight status ranges from 6%-73%. When examining overweight children, less than 50% of parents identify their child as such. PURPOSE: The purpose of this study was to examine parental ability to appropriately identify their child’s BMI status and also measures of physical fitness (body composition, muscular strength, flexibility and aerobic fitness). METHODS: Subjects consisted of 200 males (10.8±2.16 years), 170 females (11.2±2.44 years) and their maternal parent. Males and females scores were compared to maternal perception of score: BMI, body composition, and fitness characteristics (muscular strength, aerobic fitness and flexibility) were categorized according to normative rankings. The maternal perception questionnaire was administered while subject’s fitness characteristics were evaluated. Data associations were examined using descriptive statistics and bivariate correlation. RESULTS: BMI, body fat and fitness characteristics ranged categorically from poor to excellent. Maternal parents ability to correctly identify fitness characteristics by categorical selection were: BMI (75.14%), body composition (46.49%), flexibility (27.57%), muscular strength (31.08%) and aerobic fitness (38.11%). The relationship between subjects scores and parental perception of scores was considered moderate to strong, as determined by Pearson correlation (BMI: r=.677, body composition: r=.603, muscular strength: r=.251, aerobic fitness: r=.389 and flexibility r=.407). CONCLUSION: In children ranging from under-weight to obese, parent’s ability to predict characteristics relative to weight and body composition is substantially better than their ability to predict fitness characteristics. Parents have a strong influence on children’s behavior and physical activity levels. Primary prevention is key in fighting the obesity epidemic, thus adult’s awareness of their child’s fitness status is imperative. As such, professional or school-based screening could be suggested as a necessary tool to identify children’s fitness characteristics for parental informative purposes.